Efektivitas Sistem Agroforestri dalam Meningkatkan Kesehatan Tanah dan Produktivitas Pertanian - Parid Pakaya; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Land degradation due to intensive agricultural practices is a serious issue threatening food security and ecosystem balance. Monoculture farming systems often lead to soil fertility decline, increased erosion, and reduced soil biodiversity. As an alternative, agroforestry has been developed to enhance agricultural productivity without compromising soil health. Agroforestry integrates agricultural crops with trees or other woody plants in a mutually beneficial system. Several studies have shown that agroforestry improves soil organic matter content, retains soil moisture, and reduces erosion and nutrient loss. This study employs a literature review method to analyze the effectiveness of agroforestry in improving soil health and agricultural productivity. Agroforestry has been found to enhance agricultural productivity through crop diversification, efficient land use, and climate change mitigation. Diversification not only strengthens food security but also increases farmers’ income by minimizing crop failure risks and enhancing nutritional value. Additionally, agroforestry optimizes land use by improving yield per unit area and reducing environmental degradation through natural resource conservation. Agroforestry also plays a crucial role in mitigating climate change by increasing ecosystem resilience, sequestering carbon, and reducing extreme weather impacts. However, the adoption of agroforestry faces challenges, including a lack of farmers’ knowledge, limited policy support, and varying environmental conditions. Addressing these barriers through improved education, supportive policies, and sustainable resource management can accelerate agroforestry adoption. With broader implementation and strong policy support, agroforestry can drive agricultural sustainability and enhance community well-being.